Studies on Schismatoglottideae (Araceae) of Borneo XXXII: Ooia paxilla, a new dwarf obligate rheophyte from Kalimantan Utara - Sin Yeng, Wong; Peter C., Boyce (Taylor & Francis Ltd., 2013)
Ooia paxilla S.Y. Wong & P.C. Boyce is described and illustrated as a new species of obligate rheophyte from shale waterfalls in Kalimantan Utara, Indonesian Borneo.